The Relationship Between Pastoral Services and Church Members’ Worship Activeness in Canaan SDA Church - Kasingku, Juwinner Dedy; Obed, Syepi (Klabat Theological Review; Vol 3 No 1 (2022): Klabat Theological Review, 2022)
The purpose of this quantitative study is to determine whether there is a link between pastoral ministry and church members’ worship participation in Canaan Airmadidi Seventh-day Adventist Church. Using the convenience sampling method, a questionnaire was distributed to 100 baptist members of the Canaan Airmadidi Seventh-day Adventist church. This research demonstrates that the pastor devotes a significant amount of time to ministering to the people of this church. Furthermore, the congregation's participation in worship is very high. It means that the church members are always involved in church services. Likewise, there is a positive and significant correlation between the pastoral ministry and the activeness of the church members in the worship program in the Canaan Airmadidi Seventh-day Adventist Church. Keywords: pastoral ministry; church members’ activeness; worship Bibliography Berhitu John, Peran Gembala Jemaat , Jurnal Jaffray , Vol. 12, No. 2, Oktober 2014. Ginger, Evans, Learning , Violence, and the Social Structure of Value , 2006. https://doi.org/10.1111/j.1469-8676.2006.tb00038.x . Gultom Elia, Elia Moderen . Bandung: Indonesia Publising House, 2009. Hutabarat, Leonard, Hubungan pengembalaan dengan pelayanan , 2010, Taken from: http://hubungan-pengenbalaan-dengan pelayanan.blogspot.co.id/. Kusnandar, Yotam, T, Khotbah adalah seni berkomunikasi . Vol. 5o, 18, 2017. Murtiningsih, Enung, Peran Pendeta Dalam Penggembalaan Umum Di Jemaat Gki Klasis Yogyakarta , 2009, Taken from http://sinta.ukdw.ac.id . Pardede, S. R.   Sikap Seorang Pelayan , 2012. Taken from: http://bejanaindah.blogspot . co.id/2012/04/hamba-atau-tuan-sikap-seorang-pelayan.html. Pardos, Milton, Pengaruh Kualitas Kepemimpinan Dan Kerohanian Seorang Pendeta Dalam Meningkatkan Kualitas Kerohanian, Pelayanan Dan Jumlah Baptisan Di GMAHK Kota Palembang, Jurnal Kanonia. 5, (1), 2013. Peraturan Jemaat , Bandung: Indonesia Publising House, 2005. Price, C, Saran-Saran Praktis Untuk Pelayanan Yang Berhasil Jakarta: Immanuel, 1993. Senduk,  Ho Lukas , Pedoman Pelayanan Pendeta , Jakarta:Yayasan Bethel, 2008. Tandiassa, Samuel, Kepemimpinan Gereja Lokal, Yogyakarta: Moriel, 2010. White, Ellen, Pelayanan Injil. Bandung: Indonesia Publising House, 1995.